Assessment of cleaning techniques and its effectiveness for controlling biodeterioration fungi on wall paintings of Maijishan Grottoes. (July 2022) - He, Dongpeng; Wu, Fasi; Ma, Wenxia; Gu, Ji-Dong; Xu, Ruihong; Hu, Junjian; Yue, Yongqiang; Ma, Qian; Wang, Wanfu; Li, Shi-Weng
Abstract: Biodeterioration is one of the main challenges in conservation of cultural heritage. This study tested and evaluated non-destructive methods to clean and control the microbial mycelia grown on the surface of wall paintings at the World Cultural Heritage Site of Maijishan Grottoes in China. Culture-dependent methods were used for isolation of fungi prior to identification by ITS rRNA gene sequences. The mycelia grown on the surface of wall paintings were removed with soft brushes under a negative pressure provided by a modified vacuum pump, and the pre-screened biocides were then selected and applied. Using a portable microscope, a microbial ATP bioluminescence detector, and a colorimeter, the effectiveness of cleaning and controlling against fungal mycelia on the wall paintings was evaluated. The results showed that the fungal isolates were dominated by Arachnomyces spp. with 92.28% sequence identity. Other major culturable fungal isolates were Parengyodontium album, Beauveria bassiana, and Scopulariopsis brumptii . The microscopic examination indicated the surface of the wall paintings was nearly free of visible fungal mycelia after the manual removal. There was a significant reduction of ATP bioluminescence before (43, 303 ± 10, 280 RLU/cm 2 ) and after (2, 833 ± 388, RLU/cm 2 ) the mechanical removal. The color difference (Δ E ∗ ab value) were less than 2.0 before and after biocide treatment, such difference could almost be ignored. Additionally, octylisothiazolinone was found to be the most efficient biocide for controlling fungal growth and could be an emergency protection measure. Furthermore, the key environmental factors that triggered periodic breakouts of the microorganisms on wall paintings were long-term higher relative humidity at the interface of earthen plaster layer and supporting sandstone during raining seasons and poor ventilation of the cave. This study provides a reference for the scientific conservation of biodeteriorated ancient wall paintings. Highlights: Mechanical and chemical methods were used to clean and control the microbial biodeterioration on wall paintings. The controlling effectiveness was evaluated with multiple portable instruments in situ. Periodic high humidity at the interface of plaster and support was the key factor to trigger microbial biodeterioration.